2003
DOI: 10.1080/0269905021000010131
|View full text |Cite
|
Sign up to set email alerts
|

Reported problems and their resolution following mild, moderate and severe traumatic brain injury amongst children and adolescents in the UK

Abstract: The families of 97 children with mild (49), moderate (19) and severe (29) traumatic brain injury (TBI), aged 5-15 at injury, were interviewed and assessed at a mean of 2.29 years postinjury and compared with 31 healthy controls. Following the TBI, 83 (85.6%) had no therapeutic input, 74 families (76.3%) had unmet information needs, particularly regarding long-term consequences. At first interview 1097 problems were reported by the TBI group. Behavioural and school problems were frequently reported by all TBI g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
3
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 23 publications
6
101
3
1
Order By: Relevance
“…[12] Studies (mainly in developed countries) that have looked at families' needs (both met and unmet) and the problems they face in relation to TBI have identified high levels of stress, lack of education regarding TBI, lack of information on how to prepare for the future, behavioural problems and prob lems at school on the part of the TBI survivor, and survivors' loss of inter est in activities, anxiety, memory problems and aggressive tempera ment. [12][13][14][15][16] Commonly reported needs, which like the reported problems can change over time, include the need for social/instrumental care, emotional care and healthcare; the need for professional and financial support and information; the need for access to relevant information regarding TBI and its consequences; and the need to be actively involved with the care of the TBI survivor. [12][13][14][15] Successful TBI support will not only benefit survivors and their family units, but can also contribute towards a reduction in future violent acts perpetrated by TBI survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Studies (mainly in developed countries) that have looked at families' needs (both met and unmet) and the problems they face in relation to TBI have identified high levels of stress, lack of education regarding TBI, lack of information on how to prepare for the future, behavioural problems and prob lems at school on the part of the TBI survivor, and survivors' loss of inter est in activities, anxiety, memory problems and aggressive tempera ment. [12][13][14][15][16] Commonly reported needs, which like the reported problems can change over time, include the need for social/instrumental care, emotional care and healthcare; the need for professional and financial support and information; the need for access to relevant information regarding TBI and its consequences; and the need to be actively involved with the care of the TBI survivor. [12][13][14][15] Successful TBI support will not only benefit survivors and their family units, but can also contribute towards a reduction in future violent acts perpetrated by TBI survivors.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Commonly reported needs, which like the reported problems can change over time, include the need for social/instrumental care, emotional care and healthcare; the need for professional and financial support and information; the need for access to relevant information regarding TBI and its consequences; and the need to be actively involved with the care of the TBI survivor. [12][13][14][15] Successful TBI support will not only benefit survivors and their family units, but can also contribute towards a reduction in future violent acts perpetrated by TBI survivors. In SA, as in many other parts of the world, inadequate information and support, along with the lack of appropriate rehabilitation facilities, places a massive care burden on unprepared family members and community care workers.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to adult TBI, prediction of outcome in survivors is described to be complex, with several factors like the injury severity [27,28], rehabilitation and social support interacting to determine the extent of residual impairments [28]. Anatomic variances to adults like a disproportional large and heavy head with weak neck muscles as well as greater flexibility of cranial bones minimize focal brain injuries but increase the risk of diffuse brain injuries [20,[29][30][31][32][33][34][35][36].…”
Section: Paediatric Tbimentioning
confidence: 99%
“…While most investigations analysing "outcome" as key parameter have examined patients after TBI between one and three years [7,27,57,69,89], only few studies have investigated long-term outcome [7,20,21,30,90,91]. Interestingly, these studies focused severe TBI almost exclusively.…”
Section: Outcomementioning
confidence: 99%
“…The results also showed that many children with severe TBI did not exhibit deficits in more than one of the domains used to measure outcome from 6 or 12 months post-injury to 4 years post-injury, revealing that variability within the severe group could be missed if results are only studied on the group-level. Hawley (2003) interviewed the families of 97 children with mild, moderate and severe TBI, admitted to hospital for 24 hours or more. The interviews took place 2 years after injury with a follow up 12 months later.…”
Section: Recovery Of Functionsmentioning
confidence: 99%